The Effect of Teacher Training on the Implementation of Physical Education Instruction in Public Primary Schools in Nyamira South Sub-County, Kenya - Onyancha , Susan; Nyabero , Charles; Koros , Racheal; Oseko , Agnes (African Journal of Education,Science and Technology (AJEST), 2018)
Despite several importance of Physical education to learners, Physical education have not been well implemented in Kenyan schools especially schools in Kisii County therefore, this study aimed at evaluate challenges that hinder execution of Physical Education instruction in public primary schools in Nyamira South Sub-County, Kenya. It examines the impact of teachers’ training on the implementation of the Physical Exercise instruction in schools. The study adopted a descriptive survey research design and was guided by the Gross’s Curriculum Implementation Theory. The study adopted a descriptive survey research design and was guided by the Gross’s Curriculum Implementation Theory. Data was collected using both simple random and stratified sampling where 278 teachers from public primary school interviewed. Questionnaires were used to collect the data. In addition PE observations were successfully made in the six zones of the Sub-County. Quantitative data obtained via a questionnaire was analysed using descriptive and inferential statistics with the aid of the statistical package for social sciences (SPSS version 20). Means and standard deviations were used to describe levels of teacher training in PE. Thematic analysis was employed to analyse recurrent themes emanating from PE lesson observations. From the findings, it emerged that most of the teachers had certificate qualification and their knowledge and skills were acquired in college or higher levels of training. The proper training exposes public primary school teachers to proper PE instruction practices, such as, planning for PE instruction, use of diverse instructional techniques and knowledge of basic positioning skills. Therefore, teacher training was not a hindrance to implementation of PE. Nevertheless, teachers still showed apathy towards teaching the subject. This is contrary to an earlier finding from reviewed literature that teacher training is a predictor of implementation of PE instruction. The study recommends the need to maximize on the proper training in PE so that every teacher feels motivated to teach the subject. Moreover, similar studies should be replicated in public primary schools in other sub-counties so as to improve external validity of the findings. The knowledge gained from such studies will help stakeholders, parents, pupils and school personnel to make informed decisions concerning physical education.